Is international law international? - Roberts, Anthea (Writer on international law) (New York, NY : Oxford University Press, 2017)
This book challenges the idea that international law looks the same from anywhere in the world. Instead, how international lawyers understand and approach their field is often deeply influenced by the national contexts in which they lived, studied, and worked. International law in the United States and in the United Kingdom looks different compared to international law in China and Russia, though some approaches (particularly Western, Anglo-American ones) are more influential outside their borders than others. Given shifts in geopolitical power and the rise of non-Western powers like China, it.
The divisible college of international lawyers -- Project design -- Comparing international law academics -- Comparing international law textbooks and casebooks -- Patterns of difference and dominance -- Disruptions leading to a competitive world order.
Includes bibliographical references and index.
Keywords: International law; LAW -- International; International law; Electronic books